Study of Ammonia, Phosphate, Nitrate and Catfish (Clarias sp) Production on Aquaponics and Conventional Systems in Archipelagic Dry Land Areas - Nggaluama, Abram; Santoso, Priyo; Lukas, Ade (MultiTech Publisher, 2024)
This study aims to determine ammonia, phosphate and nitrate catfish (Clarias sp) farming water in aquaponics systems with conventional systems and determine catfish farming production aquaponics systems and conventional systems. The main parameters observed are ammonia, phosphate, nitrate and fish production while supporting parameters are temperature, pH, DO, SR and fish growth. The results of the independent t test showed that the value of ammonia, phosphate nitrate and nitrate in the aquaponic system was lower (P<0.05) than the conventional system, while fish production in the aquaponic system was higher (P<0.05) than the conventional system. This research shows that aquaponic systems are suitable for development in the archipelagic dry land area.